Exercise and physical activity for people with Progressive Supranuclear Palsy: a systematic review. (January 2020) - Slade, Susan C; Finkelstein, David I; McGinley, Jennifer L; Morris, Meg E
Objective: To conduct a systematic review to evaluate exercise and structured physical activity for people living with Progressive Supranuclear Palsy. Data sources: AMED, CINAHL, Cochrane, EMBASE, Informit, MEDLINE, PEDro, PsycINFO, PubMed and SportDiscus were searched until 18 August 2019. Reference lists of included studies were hand-searched. Methods: Cochrane guidelines informed review methods. English language peer-reviewed studies of any design, in any setting, were included. Method quality was appraised with the Physiotherapy Evidence Database scale and Joanna Briggs Institute instruments. Data were extracted for study design, sample characteristics and therapy content. Effectiveness was calculated where possible. Results: Eleven studies were included. Method appraisal showed moderate to high risk of bias. Research designs included three randomized controlled trials, two quasi-experimental studies, one cohort study, four case studies and one case series. Sample sizes ranged from 1 to 24. Exercise interventions included supported and robot-assisted gait training, gaze training, balance re-education and auditory-cued motor training. Dosage ranged from two to five sessions per week over four to eight weeks. End-of-intervention effect sizes were small (6-minute walk test: –0.07; 95% confidence interval (CI): –0.87, 0.73) to moderate (balance: –0.61; 95% CI: –1.40, 0.23; Timed Up and Go: 0.42; 95% CI: –0.49, 1.33) and statistically non-significant. Function, quality of life and adverse events were inconsistently reported. Conclusions: For people with Progressive Supranuclear Palsy, robust evidence was not found for therapeutic exercises. Reported improvements in walking were derived from two clinical trials. The effects of structured physical activity for people with advanced Progressive Supranuclear Palsy are not known.